APPLICATION OF PARAMETRIC DESIGN IN PROJECT CONTAINING STEEL STRUCTURES: PARAMETRIC LIGHT‐RAIL STEEL BRIDGE. Issue 3 (16th September 2019) - Nordestgaard, Peter Madsen; Jensen, Jesper; Mortensen, Peter; Wyrtz, Mikkel; Mikulenas, Mantas; Trifan, Alexandru Eugen
ABSTRACT: Traditionally, engineers await for a locked geometry from architects before modeling work starts. This is to avoid many changes and thereby risk of wasting time and money in the traditional manual way of working. With parametric design, we set up the design to cope with many changes and it is therefore adaptable for projects with many changes. With the parametric approach, we deliver a 3D model and FEM calculations model in the early project phases without any time wasted for the coming changes in the project geometry. These early models are to great benefit for all participants in the project as decisions regarding design, buildability and economics can be made on a more well founded basis. A model generated parametrically means in basic terms that the model is set up as a program script, with various input parameters. The model is generated by running this script. Thereby any changes in input parameters will only result in a dynamic real time change of the model. The time used to generate a parametric script for a given project, can be saved multiple times later in the project. Time is particularly saved if the project contains several similar structures, which can be generated by the same of parts of the same parametric script. In MOE, we have experience from various projects containing parametric design scripting. In this article, we will focus on one example, a steel light‐rail bridge.